Managers perception of hospital employees’ effort-reward imbalance - Heming, Meike; Siegrist, Johannes; Erschens, Rebecca; Genrich, Melanie; Hander, Nicole R.; Junne, Florian; Küllenberg, Janna; Müller, Andreas; Worringer, Britta; Angerer, Peter (Journal of occupational medicine and toxicology, 2023)
Hospitals are frequently associated with poor working conditions that can lead to work stress and increase the risk for reduced employee well-being. Managers can shape and improve working conditions and thereby, the health of their teams. Thus, as a prerequisite, managers need to be aware of their employees’ stress levels. This study had two objectives: At first, it aimed to test the criterion validity of the Effort-Reward Imbalance (ERI) questionnaire measuring psychosocial workload in hospital employees. Secondly, mean scales of the ERI questionnaire filled in by employees were compared with mean scales of an adapted ERI questionnaire, in which managers assessed working conditions of their employees.
Veröffentlicht: 06. Juni 2023
Gesehen am 26.07.2023